Chronic care, health care systems, and services integration - Kronenfeld, Jennie J. (Amsterdam ; Boston : Elsevier JAI, 2004)
The theme of this volume is chronic care, health care systems and services integration. The volume is divided into three sections. The first section focuses on issues that relate to health care providers. The second section contains papers that deal with home and community based services for the elderly and those who need chronic care. The third section provides lessons from countries outside the United States related to the overall themes of chronic care, systems integration and services integration. These are themes of growing importance in the US health care system as well as in health care systems in most other developed nations. The aging of populations, already underway, and expected to increase in the coming decades will bring changes and challenges to the health care system. Many of these challenges relate to chronic care needs, since chronic care needs are more important in the elderly than in other population groups, although chronic care problems are not limited to the elderly. Once people reach their 40s and 50s, they begin to develop chronic problems. Chronic problems often require both more health care services and more complicated health care services, and thus place an emphasis on services integration.
Health care systems : issues of chronic care and systems integration / Jennie Jacobs Kronenfeld -- The effects of care management effectiveness and practice autonomy on physicians' practice and career satisfaction / Thomas T. H. Wan, Yen Ju Lin and Bill B. L. Wang -- Public support for rural health care : federal programs and local hospital subsidies / Mary K. Zimmerman and Rodney McAdams -- Too poor to get sick? : the implications of place, race and costs on the health care experiences of residents in poor urban neighborhoods / Sandra L. Barnes -- Changing health care experiences and perspectives of older adults : comparisons of HMO and fee-for-services enrollees / Eva Kahana ... [et al.] -- The formulary, physician and pharmacist : managing and delivering outpatient drug benefits / Maurice Penner, Susan J. Penner and William Keck -- Older person's expectations and satisfaction with home care : theoretical origins and uncharted realms / Eileen J. Porter -- The effects of race and gender on predicting in-home and community-based service use by older Americans / Man Wai A. Lun -- Service system integration : panacea for chronic care populations? / Teresa L. Scheid -- Sense of coherence and mental health service utilization : the case of family caregivers of community-dwelling cognitively-impaired seniors / Neale R. Chumbler ... [et al.] -- The emergence of self-managed attendat services in Ontario : direct funding pilot project -- an independent living model for Canadians requiring attendat services / Karen Yoshida ... [et al.] -- Who crashes onto dialysis? : health determinants of patients who are late referred to chronic renal care in Canada / Nancy Blythe and Cecilia Benoit -- Who advocates for patients when health care systems fail? : ensuring access to essential medicines in South Africa (and the U.S.) / Melanie E. Campbell and Peri J. Ballantyne -- At first you will not succeed : negotiating for care in the context of health reform / Ivy Lynn Bourgeault ... [et al].
Includes bibliographical references.
Description based on print version record.
Keywords: Chronically ill -- Care; Older people -- Care; Long-term care of the sick; Health services administration; Health systems & services; Medical -- Health Care Delivery; Social Science -- Sociology -- General; Electronic books